AN INITIAL INVESTIGATION INTO THE DIVERSITY OF PANDANACEAE IN TUARAN, SABAH - Akmal, Raffi (Sabah Parks, 2025)
This preliminary study investigated the diversity of Pandanaceae in Tuaran, Sabah, with emphasis on species richness and their uses. The rapid assessments led to the identification of two species, Benstonea gibbsiana and Pandanus odorifer as well as the documentation of one ethnobotanical use, highlighting the cultural significance of pandan to the local community in Kampung Penimbawan. These findings contribute to baseline data on Tuaran’s Pandanaceae diversity and traditional knowledge, thus providing a foundation for future research in plant diversity and ethnobotany.